Feasibility of preservation of superior rectal artery plus dissection of lymph nodes around inferior mesenteric artery in laparoscopic resection for sigmoid colon cancer - Ren, Haoyuan; Liu, Yong; Zhang, Mingran; An, Liang (Frontiers in Surgery, 2023)
Background: Limited data are available about superior rectal artery (SRA) preservation in laparoscopic resection for sigmoid colon cancer (SCC). This study aimed to evaluate the short-term and long-term efficacies of SRA preservation in laparoscopic radical resection for SCC. Methods: We retrospectively analyzed 207 patients with SCC who underwent laparoscopic radical resection for SCC from January 2017 to June 2021. A total of 84 patients received lymph node clearance around the inferior mesenteric artery (IMA) root (D3 lymph node dissection) with preservation of SRA (SRA preservation group), and 123 patients received high ligation of the IMA (control group). The clinicopathological data of the two groups were compared, and Kaplan–Meier method was performed to estimate patient survival. Results: Compared with the control group, the operation time of the SRA preservation group was longer (p<0.001), but the postoperative exhaust and defecation times were significantly shorter (p=0.003, p<0.001). Two cases of postoperative ileus and four cases of anastomotic leakage were observed in the control group, whereas the SRA preservation group had none. However, no statistical difference was observed between the groups (p=0.652, p=0.248). The overall survival also showed no significant difference in (p=0.436). Conclusions: Preservation of SRA plus dissection of lymph nodes around IMA did not increase postoperative morbidity and mortality nor affect the prognosis of patients but increased the bowel blood supply, which may have a significant positive effect on the recovery of postoperative intestinal function and reduction of anastomotic leakage.